Patriotic upbringing as a defining factor of Personality formation - Katshibekova Zh5, Ybyraimzhanov К1, Zhabykbayeva D2, Asanbekova G3, Shakirova A4, (Opción, 2019)
The article deals with the problems of the transformation of thespiritual and cultural values of society from the point of view of newapproaches to the current stage of the socio-political development ofKazakhstan via comparative qualitative research methods. As a result,a citizen with a capital letter, seek to obtain new knowledge, masteringnew technologies, easily processing the flow of new information. Inconclusion, an appeal to scientific research in the provision of thepatriotic upbringing of students is a socio-pedagogical problem.